Development and Validation of a Decision-Making Stratification Algorithm to Optimize the Use of Rapid Diagnostic Testing for Patients with Staphylococcus Bacteremia - Thamer A. Almangour; Abdullah A. Alhifany; Deanne E. Tabb (Canadian Journal of Infectious Diseases and Medical Microbiology)
Purpose. To evaluate whether introducing rapid diagnostic testing in conjunction with implementing a stratification algorithm for testing eligibility would be an appropriate clinical and cost saving approach. Method. An internal concurrent 4-month observational study was performed. Positive blood cultures continued to be worked up in accordance with standard of care. An additional call to the infectious disease (ID) pharmacy service occurred for all positive blood cultures with Gram-positive cocci in clusters (GPCC). The ID pharmacy service investigated each case using a prespecified stratification algorithm to minimize unnecessary use of rapid identification testing. Results. 43 patients with GPCC were screened. Only nine patients met inclusion criteria for QuickFISH™ testing. The average expected time avoided to optimize antibiotic therapy is 35±16 hours. If the QuickFISH test had been indiscriminately implemented for all cases, the cost for performing this test would have been $5,590. However, using the prespecified algorithm, only 9 patients were tested for a projected cost of $1,170. Conclusion. Introducing rapid diagnostic testing in conjunction with implementing patient stratification algorithm for rapid identification of GPCC from blood cultures in addition to the ID pharmacy intervention will provide a positive impact on the clinical and economic outcomes in our health care setting.